Strength and power predictors of sprinting performance in professional rugby players - Cunningham, D. J.; West, D. J.; Owen, N. J.; Shearer, D. A.; Finn, C. V.; Bracken, R. M.; Crewther, B. T.; Scott, P.; Cook, C. J.; Kilduff, L. P. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The ability to accelerate and attain high levels of speed is an essential component of success in team sports; however, the physical qualities that underpin these activities remain unclear. This study aimed to determine some of the key strength and power predictors of speed within professional rugby union players. Methods: Twenty professional male rugby union players participated in this study. Subjects were tested for speed (0-10 m sprint and a flying 10 m sprint), strength (3 repetition maximum squat), lower body power (countermovement jumps [CMJ] and drop jumps [DJ]), reactive strength and leg spring stiffness. The strength and power variables were expressed as absolute values and relative values for analysis. Results: Both relative strength (r=-0.55, PConclusion: This study provides an insight into those physical attributes that underpin sprinting performance in professional rugby union players and specifically highlights the importance of relative strength and power in the expression and development of different speed components (e.g. acceleration, maximum velocity).